Study protocol for NCCH1908 (UPFRONT-trial): a prospective clinical trial to evaluate the feasibility and utility of comprehensive genomic profiling prior to the initial systemic treatment in advanced solid tumour patients. (8th October 2021) - Mizuno, Takaaki; Yoshida, Tatsuya; Sunami, Kuniko; Koyama, Takafumi; Okita, Natsuko; Kubo, Takashi; Sudo, Kazuki; Shimoi, Tatsunori; Ueno, Hideki; Saito, Eiko; Katanoda, Kota; Shibata, Taro; et al.
Abstract: : Comprehensive genomic profiling has been approved for use in patients with advanced solid tumours; however, it is only indicated in advanced solid tumour patients without available standard chemotherapeutic treatment or those who have completed standard treatments in Japan, and there are no available data on the clinical feasibility and utility of comprehensive genomic profiling in treatment-naive patients. This multicentre, single-arm, prospective study aims to evaluate the feasibility and utility of the OncoGuide NCC Oncopanel System in treatment-naive patients with six advanced major malignancies: non-small cell lung cancer, breast cancer, gastric cancer, colon cancer, pancreatic cancer and biliary tract cancer (NCCH1908). This study (study cohort) will be compared with the other prospective observational study (control cohort), which enrols patients not receiving comprehensive genomic profiling prior to initial systemic treatment. A total of 200 patients will be enrolled in the study over 21 months. This study has been registered in the UMIN Clinical Trials Registry (www.umin.ac.jp/ctr/ ) (UMIN000040743). Clinical trial registration: This study, initiated in June 2020, has been registered in the UMIN Clinical Trials Registry (www.umin.ac.jp/ctr/ ) (registration number: UMIN000040743). We plan to enrol a total of 200 patients over a period of 21 months. Abstract : This multicentre, single-arm, prospective study will evaluate the feasibility and utility of the OncoGuide NCC Oncopanel System in treatment-naive patients with six major advanced/recurrent solid malignancies.